Scandalum in the early Bolognese decretistic and in papal decretals (ca. 1140-1234) - Druwé, Wouter (Spicilegium sacrum Lovaniense, 2018)
Publisher's description: The wish to avoid scandala or to put an end to scandalous situations has been and remains a continuous concern of canonists and Church authorities, at least as of the thirteenth century. As of Raymond of Penafort's Summa de paenitentia (late 1220s - early 1230s), scandalum was dealt with separately in canonical dictionaries. Legal historical research on the earlier use of the term within canon law, is however relatively scarce. Inspired by the linguistic-philosophical approach of the Begriffsgeschichte, this book offers a conceptual-historical analysis of the use of scandalum by early Bolognese decretists (ca. 1140 - ca. 1180) and in papal decretals from Alexander III (1159) until the promulgation of the Liber Extra by Gregory IX in 1234. For Gratian and the earliest generation of decretists (Paucapalea and Rolandus), scandalum was a quite insignificant notion. Gradually, with Rufinus, however, the concept gained importance, both quantitatively and qualitatively. Stephen of Tournai pointed at the horrible consequences of a scandalum for the salvation of the souls. Simon of Bisignano stressed, for instance, the opposition between scandalum and peace. Even though non of the twelfth- and early thirteenth-century sources had yet developed a consistent theory on scandalum and its legal consequences, the analysis of papal decretals shows how scandalum became a more popular concept, especially in the field of disciplinary and penal canon law. Some evidence even suggests an instrumentalism of the term by the end of the twelfth century. At the same time, increasingly popes, especially Innocent III (1198-1216), were aware of the ambivalent nature of the concept. Apart from scandalum's polysemy, the legal-political use of the term was striking: repression, reconciliation and cover-up policies could all be justified in order to avoid or to put an end to scandala, and, thus, to save one's soul and to protect the Church. This relatively open and flexible notion played an important part in the Church's peace policy as well. This study argues that scandalum can be described as 'indignation as a source of conflicts'